Demographic profile of COVID-19 positive mothers & their outcome in government Rajaji hospital, Madurai, Tamilnadu - A cross sectional Study - C. Brinda Priyadharshini; S. Priya; M. Selvameena; S. Waseemsha; E. Muthurajesh; M. Shalini (Elsevier, 2021)
Background: COVID-19 is a new pandemic disease. This disease course and its effect on pregnancy is little known due to limited available data. The objective of this study was to describe the demographic profile of COVID-19 positive mothers admitted in Government Rajaji hospital, Madurai in terms of time, place and person and to assess the general and pregnancy outcome of study population. Methods: This cross-sectional study was done among 381 COVID-19 positive mothers* admitted during March 22 - August 31, 2020 in dedicated COVID-19 hospital, Madurai. Data was collected using Case Investigation Form (CIF) as a part of Rapid Response Team*(RRT) by Community Medicine* Department and analysed using SPSS version 21. Descriptive statistics done; Chi-square test & Fischer exact test was done to find out association between patient profile and outcomes. Results: Out of 381, 154 (40.4%) belonged to 21-25 years, 192 (50.4%) to rural area, 318 (83.5%) to 3rd trimester,189 (49.6%) Primi gravida. 125 (32.8%) were symptomatic and 153 (80.8%) had at least one comorbidity. Death as general outcome was 3 (0.8%), all of them were referred cases and had comorbidity like GDM/PIH. 10 (2.62%) had abortion or perinatal death, 14 (3.77%) had preterm delivery, 99 (25.98%) babies were born small for gestational age. Increased maternal age had more death but was not statistically significant; All symptomatic mothers (p = 0.000),1st & 2nd trimester (p = 0.000) mothers had statistically significant poor pregnancy outcome*. Conclusion: COVID positive mothers with increased age, symptomatic, 1st & 2nd trimester were significantly associated with poor outcome, requires special attention. Early referral must be emphasized to mitigate maternal death.